Are there benefits to diversification across the largest African stock markets? - De Jesus, Carlos (University of Cape Town, 2016)
This study examines the co-movements of selected African stock exchanges, including Nigeria, Morocco, Egypt and South Africa, as well as the USA, in local currency and in USDt erms, for the period January 2004 to June 2014. The study sheds light on African market cointegration before, during, and post the financial crises of 2007/2008 to identify whether there are benefits to diversification in stock exchanges across Africa and how this has changed over time. Only the four biggest exchanges are examined, to eliminate the effects of illiquidity and ensuring the size of indices used result in conclusions that are practical to investors. This study looks at short and long term relationships using correlation, cointegration, and the direction of the relationships using causality tests. It finds low correlations between all African exchanges and the USA, with the exception of South Africa, which did show significant correlation with the USA. We find no consistent cointegration relationships over the periods tested. There are no consistent causality relationships between the various countries. The implication of these results are that there are likely benefits to diversification across the four African exchanges examined.